Color in the classroom how American schools taught race, 1900-1954 - Burkholder, Zoe (Oxford University Press, 2014)
Between the turn of the twentieth century and the Brown v. Board of Education decision in 1954, the way that American schools taught about ""race"" changed dramatically. This transformation was engineered by the nation's most prominent anthropologists, including Franz Boas, Ruth Benedict, and Margaret Mead, during World War II. Inspired by scientific racism in Nazi Germany, these activist scholars decided that the best way to fight racial prejudice was to teach what they saw as the truth about race in the institution that had the power to do the most good-American schools.